Peran Saksi Ahli Psikolog Anak dalam Pembuktian di Peradilan terhadap Anak Korban Pemerkosaan - Fadhilla Fajrah; Muhammad Khadafi; Rodia Afriza (Universitas Muhammadiyah Metro, 2025)
Child victims of rape are a vulnerable group who experience severe psychological impacts and therefore require special protection in judicial proceedings. In the context of legal evidence, children’s testimonies often face limitations related to psychological conditions and cognitive development. Thus, the role of child psychologist expert witnesses is crucial in assisting law enforcement officials to understand the psychological condition of child victims and to assess the credibility of their statements. This study aims to examine the role of child psychologist expert witnesses in the evidentiary process in court involving child victims of rape. This research employs a qualitative method with a juridical-psychological approach through literature review and legal document analysis. The findings indicate that child psychologist expert witnesses play an important role in explaining the psychological condition of victims, trauma impacts, children’s capacity to testify, and providing recommendations for psychological protection during legal proceedings. The presence of child psychologist expert witnesses assists judges in evaluating evidence comprehensively and prioritizing the best interests of the child.